Maternal near miss, mortality and their correlates at tertiary care hospital - Tayyiba Wasim; Gul e Raana; Mustafa Wasim; Javeria Mushtaq; Zeenish Amin; Saman Asghar (Journal of the Pakistan Medical Association, 2021)
OBJECTIVE: To determine the frequency and causes of maternal near miss and mortality among pregnant women. METHODS: This cross-sectional study was conducted Jan 2016 - Dec 2018. All near miss cases, admitted in Gynecology department of Services Hospital Lahore during the study period, were prospectively recruited. WHO criteria was used to identify maternal near miss cases. Primary outcome measures were frequency and causes of near miss and maternal mortality to near miss ratio. Secondary outcome measures were delays, need for massive blood transfusion, ICU admission, obstetric hysterectomy and hospital stay> 7 days. RESULTS: During the study period, there were 10,739 live births, 305 near miss cases and 29 maternal deaths. Frequency of near miss was 28.4/ 1000 live births and maternal mortality to near miss ratio was 1:10.5. There were 215(70.4%) unbooked patients and 23(79.3%) of them died (p<0.001). Hemorrhage accounted for 150 (49.18%), hypertensive disorders 102 (33.44%),cardiac disease 25 (8.28%) and infection for 12 (3.97%) near miss cases respectively. Maternal mortality was significantly low for hemorrhage, hypertension, sepsis and cardiac disease; 6 vs 150, 8 vs102, 3vs 12 and 10 vs 25 respectively (p<0.001). Massive blood transfusion was given to 20.98%patients, 15.74% underwent hysterectomy, 32.13% required ICU admission. First and second delay was seen in 78.6% of patients with 86.2% deaths (p<0.001) CONCLUSION: Hemorrhage and hypertension are major reasons for near miss but timely intervention can prevent mortality. Strengthening care at primary and secondary level can reduce the burden of maternal morbidity. Continuous....